Robustness assessment of frame structures using simplified beam and grillage models. (15th May 2016) - Stylianidis, P.M.; Nethercot, D.A.; Izzuddin, B.A.; Elghazouli, A.Y.
Highlights: The objective of the study is to identify effective methods for enhancing structural robustness. The progressive collapse behaviour of steel and composite buildings is examined. Simplified beam and grillage models developed in previous studies are adopted. It is confirmed that catenary action is usually prevented by premature failure. It is found that substantial connection strength is required for securing structural robustness. Abstract: Simplified analysis methods derived in previous studies are employed for studying the progressive collapse behaviour of steel and composite buildings. A regular frame building is considered and various scenarios of sudden column removal, each affecting different floor areas in terms of geometry and boundary conditions, are applied. Descriptions of the pseudo-static responses of the various constitutive beams are obtained based on both detailed representations of the nonlinear static responses and by applying a new simplified approach proposed in a separate publication. Comparisons between the results of the two methods confirm that the simplified approach is capable of describing behaviour with reasonable accuracy. By employing a simplified multi-level assessment approach that has been previously derived at Imperial College, grillage-type approximations are obtained and used to examine the floor dynamic behaviour for the various column removal cases. It is found that, although the structural response varies depending on the location of the initial damage, substantial connection strength is required in all cases in order to provide resistance to progressive collapse. In addition, for average levels of connection ductility, failure most likely occurs prior to the development of tensile catenary action in the beams, which indicates that the provision of tying resistance may not be effective in enhancing robustness. Therefore, the combined action of flexure and compressive arching in the beams is likely to form the principal collapse resisting mechanism in common practical applications, which confirms similar conclusions made in previous studies at Imperial. The provision of adequate levels of connection moment capacity – in combination with sufficient ductility supply – is, therefore, the most effective way of securing structural robustness.